Association of Myocardial Changes and Gene Expression of the NFATC1 and NFATC4-Calcineurin Signaling Pathway in Children with Bicuspid Aortic Valve - Kamenshchyk, A. V.; Gonchar, M.; Oksenych, V.; Kamyshnyi, A.; Каменщик, Андрій Володимирович (My University, 2023)
The role of NFATC gene expression in bicuspid aortic valve (BAV) progression is not fully understood. The aim of this study is to determine the significance of NFATC1 and NFATC4 gene expression for myocardial changes in children with BAV. Methods: In 47 children with BAV, the standard Doppler echocardiographic characteristics were detected, and the expression of the NFATC1 and NFATC4 genes was studied. Results: Posterior wall thickness in diastole (PWTd) and aortic valve peak pressure gradient (AoPPG) in BAV patients were significantly higher compared to healthy controls (PWTd median (min–max), 9 (7–10) mm vs. 7 (6–8) mm; and AoPPG median (min–max), 7.79 (2.98–15.09) mm Hg vs. 2.94 (2.42–3.72) mm Hg). The expression of the NFATC1 gene in BAV children was significantly higher compared to NFATC4 (NFATC1 median (min–max); 70.88 (8.79–106.51) e.u. vs. 7.72 (1.74–22.67) e.u., respectively p < 0.05). A significant correlation of NFATC1 expression with Ao found (R = +0.53, p < 0.05). In BAV patients with PWTd > 8 mm and Ao > 21 mm the NFATC1 expression was significantly higher compared to those with PWTd 8 mm and Ao 21 mm (NFATC1 median (min–max); 45.49 (5.01–101.52) e.u. vs. 15.53 (2.36–44.40) e.u., p < 0.05 and 81.11 (20.27–101.10) e.u. mm vs. 12.16 (2.40–45.49) e.u., p < 0.05, respectively). Conclusion: In children with BAV the high expression of the NFATC1 calcineurin signaling pathway gene is associated with elevated PWTd and Ao.
Keywords: bicuspid aortic valve; children; NFATC1 gene expression; myocardial changes; posterior wall thickness; aorta